2017
DOI: 10.1016/j.advwatres.2017.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical characterisation of the groundwater–surface water interface

Abstract: Interactions between groundwater (GW) and surface water (SW) have important implications for water quantity, water quality, and ecological health. The subsurface region proximal to SW bodies, the GW-SW interface, is crucial as it actively regulates the transfer of nutrients, contaminants, and water between GW systems and SW environments. However, geological, hydrological, and biogeochemical heterogeneity in the GW-SW interface makes it difficult to characterise with direct observations. Over the past two decad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(53 citation statements)
references
References 257 publications
(343 reference statements)
0
50
0
Order By: Relevance
“…Subsequent research has showed the potential of this technique for estimating vertical exchanges by measuring thermal profiles with a higher depth resolution [72], or obtaining spatial flux patterns within the shallow streambed at relatively high resolution [73,74]. Combining FO-DTS with other techniques, such as thermal infrared reflectometry (TIR) [75] or geophysics [74,76,77] can provide insights into the impacts that the hydrogeological characteristics of the subsurface material can have on defining exchange patterns (i.e., to inform about the existence of different components of groundwater-surface water interactions, such as groundwater discharge, interflow, and local downwelling, depending on the hydrogeology) [74].…”
Section: Physical Drivers Of Hyporheic Exchange Flowsmentioning
confidence: 99%
“…Subsequent research has showed the potential of this technique for estimating vertical exchanges by measuring thermal profiles with a higher depth resolution [72], or obtaining spatial flux patterns within the shallow streambed at relatively high resolution [73,74]. Combining FO-DTS with other techniques, such as thermal infrared reflectometry (TIR) [75] or geophysics [74,76,77] can provide insights into the impacts that the hydrogeological characteristics of the subsurface material can have on defining exchange patterns (i.e., to inform about the existence of different components of groundwater-surface water interactions, such as groundwater discharge, interflow, and local downwelling, depending on the hydrogeology) [74].…”
Section: Physical Drivers Of Hyporheic Exchange Flowsmentioning
confidence: 99%
“…; McLachlan et al . ). They form a continuum which controls aquatic ecosystem along with water quality and quantity.…”
Section: Introductionmentioning
confidence: 97%
“…Theories such as fractal transport are founded on knowledge of the probabilistic properties of the flow media [1] and [2]. As a potential measure of circumventing the high cost, [3] and [4] had conjectured that cheaper, minimally invasive and technically robust geophysical data ought to supplement hydraulic data. References [1] and [5] proposed a means of modeling groundwater flow dynamics based on crossover statistics of groundwater head fluctuations.…”
Section: Introductionmentioning
confidence: 99%